A Contingent Valuation Approach to Community-based Watershed Management in Beyşehir Lake Basin - Fadim Yavuz Ozdemir; Tüzin Baycan-Levent (European Regional Science Association (ERSA), 2010)
Community-based watershed management has become more predominant as part of the trend towards more holistic and participatory approaches to water resources management. Locally based planning at the watershed scale is seen as an operative way to enhance long-term water resources management and environmental sustainability. Large-scale (regional) ecological systems can be most effectively regulated by small-scale (local) social organizations. Consequently motivating local people to actively participate in controlling non-point source pollution through integrative watershed management is important. Beyşehir Lake is the largest freshwater lake and drinking water reservoir in Turkey. The lake, located in the southwest of Konya Closed Basin, is significant both for humans, as a source of fresh water, and environmentally, due to the wetland ecosystem. Beyşehir Lake Basin (BLB) suffers from lots of environmental and socio-economic problems. Variations in water level due to inappropriate water policy and non-point source pollution in the lake have become striking environmental issues at the basin. This paper aims to explore the knowledge and perceptions of the local people about non-point source pollution and community-based watershed management policies in BLB. In this context local people's; i) awareness level concerned with BLB problems, ii) attitudes toward non-point source pollution control and watershed management, iii) the socio-economic factors affecting the residents' participations to watershed management, and iv) proposal strategies to provide sustainability of the basin, and finally v) willingness to pay (WTP) for improving Beyşehir Lake's water quality and quantity is evaluated. The contingent valuation method (CVM) is used to estimate economic value of improving local watershed services for BLB residents. The findings highlight the awareness level, attitude and preference differences between the people live nearby the lake and far from the lake. A better understanding of local people's knowledge and attitudes toward the watershed management is expected that will greatly help the integration of social progress and stability, economic development and natural resource management, in this way sustainability of the basin.
Keywords: 330; Community-based Watershed Management; Non-Point Source Pollution; Beyşehir Lake Basin; Contingent Valuation Method (CVM)